Peptide conformational imprints enhanced the catalytic activity of papain for esterification - Kanubaddi, Kiran Reddy; Yang, Ching-Lun; Huang, Pei-Yu; Lin, Chung-Yin; Tai, Dar-Fu; Lee, Chia-Hung (Frontiers in Bioengineering and Biotechnology, 2022)
Peptide conformational imprints (PCIs) offer a promising perspective to directly generate binding sites for preserving enzyme with high catalytic activity and stability. In this study, we synthesized a new chiral cross-linker cost-effectively, for controlling the matrix morphology of PCIs on magnetic particles (PCIMPs) to stabilize their recognition capability. Meanwhile, based on the flank part of the sequences on papain (PAP), three epitope peptides were selected and synthesized. Molecularly imprinted polymers (MIPs) were then fabricated in the presence of the epitope peptide using our new cross-linker on magnetic particles (MPs) to generate PCI on MPs (PCIMPs). PCIMPs were formed with helical cavities that complement the PAP structure to adsorb specifically at the targeted position of PAP. PCIMPs65-79 was found to have the best binding parameters to the PAP as Kd = 0.087 μM and Bmax = 4.56 μM. Upon esterification of N-Boc-His-OH, proton nuclear magnetic resonance (1H-NMR) was used to monitor the yield of the reaction and evaluate the activity of PAP/PCIMPs. The kinetic parameters of PAP/PCIMPs65-79 were calculated as Vmax = 3.0 μMs-1, Km = 5×10-2 M, kcat = 1.1×10−1 s-1, and kcat/Km = 2.2 M-1s-1. In addition, PAP is bound tightly to the PCIMPs to sustain its activity after four consecutive cycles.